2015
DOI: 10.1136/injuryprev-2015-041581
|View full text |Cite|
|
Sign up to set email alerts
|

Risk and protective factors for falls on one level in young children: multicentre case–control study

Abstract: BackgroundChildhood falls are an important global public health problem, but there is lack of evidence about their prevention. Falls on one level result in considerable morbidity and they are costly to health services.ObjectiveTo estimate ORs for falls on one level in children aged 0–4 years for a range of safety behaviours, safety equipment use and home hazards.Design, setting and participantsMulticentre case–control study at hospitals, minor injury units and general practices in and around four UK study cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Finding that higher educated parents were more knowledgeable regarding child falls` prevention and management compared to lower educated parents is consistent with findings of a systematic review who documented that families with low socioeconomic status were more associated with fall injuries risk factors [7]. Also other studies confirmed that low socio-economical status is a risk factor for child injury and this is explained by some structural and behavioral mechanisms [13,17].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Finding that higher educated parents were more knowledgeable regarding child falls` prevention and management compared to lower educated parents is consistent with findings of a systematic review who documented that families with low socioeconomic status were more associated with fall injuries risk factors [7]. Also other studies confirmed that low socio-economical status is a risk factor for child injury and this is explained by some structural and behavioral mechanisms [13,17].…”
Section: Discussionsupporting
confidence: 85%
“…Data were collected through a self-administrated questionnaire, created by the researcher, adopted from previous similar studies [4,13] and face validated by three consultants in Family medicine, Community medicine and pediatrics.…”
Section: Study Tool and Data Collection Technique: (Appendix 1)mentioning
confidence: 99%